2006
DOI: 10.1002/micr.20281
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical explanation of the buckling of the vessels after twisting of the microanastomosis

Abstract: In surgical practice, with the parameters of our experimental Wistar rats model (vessel diameter, length of dissection), it is fundamental to be below 105 degrees of torsion angle for the vein microanastomosis, in order to decrease its risk of failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 8 publications
(24 reference statements)
0
21
0
Order By: Relevance
“…Once all perforators have been identified, the best one is chosen based on caliber, pulsatility, course and orientation, number and caliber of accompanying veins, and proximity to the defect and to a sensory nerve (the biggest perforators usually accompany sensory nerves all over the body). Then, in cases of suprafascial dissection, the fascial opening is widened and the perforator is freed from any surrounding tissue and dissected as long as possible (up to the source vessel) in order to achieve an adequate length of the pedicle along which to distribute the torsion [17]. Care should be taken in order to divide any attachment of the perforator to the surrounding tissues, like side branches (that must be ligated and not cauterized to avoid thermal damage to the perforator) or fibrous bands.…”
Section: Resultsmentioning
confidence: 99%
“…Once all perforators have been identified, the best one is chosen based on caliber, pulsatility, course and orientation, number and caliber of accompanying veins, and proximity to the defect and to a sensory nerve (the biggest perforators usually accompany sensory nerves all over the body). Then, in cases of suprafascial dissection, the fascial opening is widened and the perforator is freed from any surrounding tissue and dissected as long as possible (up to the source vessel) in order to achieve an adequate length of the pedicle along which to distribute the torsion [17]. Care should be taken in order to divide any attachment of the perforator to the surrounding tissues, like side branches (that must be ligated and not cauterized to avoid thermal damage to the perforator) or fibrous bands.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies have been less convincing, with equivocal results regarding the degree of kinking that leads to "buckling" and thrombosis (Level V Evidence). [111][112][113][114] In vivo studies show that kinking has a much greater impact in veins as opposed to arteries. Several retrospective reviews of free flap failure have shown that kinking or compression has resulted in venous thrombosis in each series of patients (Level III Evidence).…”
Section: Kinking Vein Grafts and One Versus Two Veinsmentioning
confidence: 97%
“…The human GSVs are more muscular, becomes increasingly inextensible with small increases in stretch or pressure, and have a greater thickness-to-radius ratio compared to the porcine IJVs which composed primarily of elastin and collagen, exhibits greater compliance in both the axial and circumferential directions. The effect of axial stretch ratio on vein twist has not been reported previously since it was not measured in previous studies (Endean et al 1989; Bilgin et al 2003; Selvaggi et al 2006). Our results showed that the axial stretch ratio has only modest effect on the critical twist angle of porcine veins.…”
Section: Discussionmentioning
confidence: 82%
“…The current results demonstrated that the two-fiber model can be used for blood vessel twisting deformation as well as (symmetric) inflation and axial stretch. It is also a big step forward as compared to previous vessel buckling simulations that used only the elastic isotropic material models (Selvaggi et al 2006; Wong et al 2007)…”
Section: Discussionmentioning
confidence: 99%